Measuring the gains from inter-regional cooperation: oerview and application - Schwarm, Walter R., author; Cutler, Harvey, advisor; Ozawa, Terutomo, committee member; Weiler, Stephan, committee member; Davies, Stephen, committee member (Colorado State University. Libraries, 2002)
This dissertation encompases a tri-fold goal: 1) To explain the theoretical and applied aspects that underlie the construction of a interjurisdictional Computable General Equilibrium (CGE) model. 2) To describe a data organizational method that allows for an easier, more effective model building experience. 3) To construct a CGE model that not only displays the value of regional analysis but also can be used to provide analytical results based on the theoretical structure. Outcomes from this model are analyzed within a game theoretic framework stressing regional cooperation The combined approach allows unusually keen insights into the tradeoffs in a regional political economy. When considering a region-wide policy, such as a growth cap. it may be the case that the jurisdictions' dominant strategy is not the one that maximizes welfare for the component cities.

This game-theoretic argument is tested using a CGE model calibrated to be consistent with the cities and region of Fort Collins, and Loveland, Colorado. By applying the actual dollar/welfare values produced by the model, the relative success of a program of regional cooperation can be evaluated and the relative welfare loss incurred by non-compliance predicted.
Keywords: urban planning; area planning and development; game theory; studies; trends; estimates; prices; local government; expenditures; simulation; cooperation; planning; decision making; regions; copyright; households; cities; public policy